2015
DOI: 10.1111/boj.12342
|View full text |Cite
|
Sign up to set email alerts
|

Floristic patterns of epiphytes in the Brazilian Atlantic Forest, a biodiversity hotspot

Abstract: To assess the main factors driving epiphytic angiosperm distribution throughout the Brazilian Atlantic Forest, we compiled 57 floristic surveys and analysed species composition under the influence of environmental variables, space and vegetation type using canonical correspondence analysis (CCA), similarity (Sorensen) and Mantel's tests. The indicator value index (IndVal) was used to find indicator species of each Brazilian Atlantic Forest vegetation type. Group sharpness analysis was performed in order to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 64 publications
(61 reference statements)
1
16
0
2
Order By: Relevance
“…A spatially structured gradient was also found in studies conducted in rocky outcrop in French Guiana and in south-eastern rock grasslands Brazil (Silva Mota et al 2018, Sarthou et al 2017. Similarly, floristic patterns of Bromeliaceae epiphytes in the Brazilian Atlantic Forest were mainly associated with space (Leitman et al 2015). This result may also be related to the dispersion capacity of some species of bromeliads, or suggest the absence of some pollinators (bats, hummingbirds, bees and butterflies), indicating that environmental constrains positively correlate with spatial distances affect the floristic differences in this spatial scale (Brown & Lomolino 2001).…”
Section: Discussionsupporting
confidence: 64%
“…A spatially structured gradient was also found in studies conducted in rocky outcrop in French Guiana and in south-eastern rock grasslands Brazil (Silva Mota et al 2018, Sarthou et al 2017. Similarly, floristic patterns of Bromeliaceae epiphytes in the Brazilian Atlantic Forest were mainly associated with space (Leitman et al 2015). This result may also be related to the dispersion capacity of some species of bromeliads, or suggest the absence of some pollinators (bats, hummingbirds, bees and butterflies), indicating that environmental constrains positively correlate with spatial distances affect the floristic differences in this spatial scale (Brown & Lomolino 2001).…”
Section: Discussionsupporting
confidence: 64%
“…The set of variables of this study were also showed to be relevant in studies dealing with biogeography and floristic relationships of angiosperm epiphytes in Atlantic Forest (Menini Neto et al 2009;Leitman et al 2015).…”
Section: Multivariate Analysesmentioning
confidence: 83%
“…The diversity of vascular epiphytes are known to vary at both local (ter Steege & Cornelissen 1989, Arévalo & Betancur 2004, Kersten et al 2009, Joanitti 2013) and on a large scale (Gentry & Dodson 1987, Nieder et al 1999, Breier 2005, Leitman et al 2015. Their distribution might follow ecological gradients, both horizontally -among different vegetation types and phorophytes (Benavides et al 2011) -and vertically, exhibiting variations on the same phorophyte, from the floor to the canopy (ter Steege & Cornelissen 1989, Nieder et al 1999, Rogalski et al 2016.…”
Section: Introductionmentioning
confidence: 99%